Unraveling the critical role of SUMOylation in the governing of tumor immunity - Liu, Xiangfei; Ding, Wei; Jiang, Lu; Chen, Qianming; Luo, Xiaobo (Frontiers in Immunology, 2025)
SUMOylation, a dynamic regulatory process in post-translational modifications (PTMs) mediated by small ubiquitin-like modifier (SUMO) ligases and deSUMOylases, regulates protein function through reversible lysine conjugation. Emerging evidence has identified tumor-mediated hijacking of SUMOylation in both malignant cells and immune components as a novel immune evasion mechanism. This review represents a comprehensive update on how tumor-intrinsic SUMOylation modulates tumor immunity-related JAK/STAT, MHC-I, NF-κB, IFN-I/II pathways and other key proteins to drive its immune evasion, and immune cell-intrinsic SUMOylation in regulating natural killer (NK) and T cell cytotoxicity, dendritic cell (DC) maturation, and macrophage polarization. Tumor immunotherapy is a new potential strategy for cancer, mainly represented by immune checkpoint inhibitions (ICIs), which exhibits poor efficacy in head and neck squamous cell carcinoma (HNSCC), pancreatic ductal adenocarcinoma (PDAC) and other solid tumors. Targeting SUMOylation of tumors presents high potential to synergistically improve the therapeutic effect of ICIs. Preclinical studies have shed light on the therapeutic potential of the combination of SUMOylation inhibitors such as TAK-981 or 2-D08 with ICIs, thus significantly improving tumor prognosis. As current phase I trials suggest dose-dependent toxicity of TAK-981, there is a need for targeted delivery systems; AI-assisted screening of novel SUMOylation inhibitors (SUMOi) which are FDA approved serves as another potential approach; besides, antibodies against these pivotal SUMOylated molecules in tumors could be conjugated with SUMOi to restore the activity of specific proteins in tumor microenvironment. In all, our review proposes that current or other novel strategies for SUMOylation inhibition stands as a promising adjuvant to immunotherapy for tumor management, thereby potentially contributing to the favorable prognosis of cancer patients.